Welfare Effects of Transparency in Foreign Exchange Markets : The Role of Hedging Opportunities - Drees, Burkhard (IMF Working Papers; Working Paper ;, 2002)
This paper studies the impact of enhanced transparency on risk sharing opportunities in the foreign exchange market and the associated implications for ex ante welfare. Transparency is measured in this model by the informational content of publicly observable signals about exchange rate developments. We find that in this model more transparency improves welfare in economies that are poorly endowed with capital and/or where investors are not very risk-averse, while welfare is reduced in economies with large capital endowments and/or where investors are highly risk-averse.